Frequency dependence of the polar motion resonance. Issue 2 (20th November 2019) - Bizouard, C; Nurul Huda, I; Ziegler, Y; Lambert, S
SUMMARY: The nutation of the Celestial Intermediate Pole can be considered as a retrograde diurnal polar motion. As the common polar motion, it presents a resonance, but with period T PM and quality factor Q PM differing from the ones characterizing the Chandler wobble ( T CW = 430.2−431.6 d, Q CW in the interval (56 255) according to Nastula & Gross): according to the nutation analysis presented in a separate paper, this period is about T PM = 380 d and the quality factor becomes −10. In this study, we aim to revisit the geophysical interpretation of this result. Two complementary factors account for the observed values: the non-equilibrium response of the ocean to the pole tide potential in the diurnal band, and the resonance of the solid Earth tide at the free core nutation period. This leads to a resonance of T PM in the vicinity of the free core nutation period, confirmed by estimates derived from nutation analysis.